Long Noncoding RNA MALAT1: Insights into its Biogenesis and Implications in Human Disease - Wu, Yuting; Huang, Cheng; Meng, Xiaoming; Li, Jun (Current Pharmaceutical Design, 2015)
Genome-wide studies have identified thousands of noncoding RNAs (ncRNAs) with no protein coding capacity. Among them, the long non-coding RNAs (lncRNAs), which are more than 200 nucleotides in length, recently are widely concerned for their crucial role in regulating biological processes and diseases. However, most lncRNAs are expressed at a very low level, and generally exhibit poor primary sequence conservation over evolution. Long non-coding RNA MALAT1 (metastasis-associated lung adenocarcinoma transcript 1), also known as NEAT2 (nuclear-enriched abundant transcript 2), is outstanding among the lncRNA family due to its evolutionarily high conservation and abundant expression throughout diferent mammalian species. Meanwhile, MALAT1 was one of the first lncRNAs that was demonstrated to be associated with a disease, namely non-small cell lung cancer (NSCLC). Subsequently, MALAT1 was identified in multiple types of physiological processes, such as alternative splicing, nuclear organization, epigenetic modulating of gene expression, and so on. Moreover, a growing number of evidences indicated that MALAT1 was also closely related to various pathological processes, ranging from diabetes complications to cancers.In this review, we will make a summary on current understanding of MALAT1 in different physiological or pathophysiological processes and discuss the potential therapeutic applications based on MALAT1 detection and inhibition.
Keywords: MALAT1